A STUDY OF TUMOR-ASSOCIATED PROTEINS IN TISSUES AND BLOOD SERA FROM BREAST CANCER PATIENTS - T. S. Bobrova (SPb RAACI, 2014)
Abstract. The study deals with p34 distribution in tissue and sera from the patients with breast cancer, using Western-blotting with МКА 1F3-2D4 monoclonals and antisera that identified p34 in breast cancer tissue samples, in metastases. In blood sera, p51-53, p150-p250 were assayed. The proteins may be associated either with cathepsin D precursors, or mucins, or cadherins, or CD22 adhesion molecule.